Processor and System-on-Chip Simulation - Leupers, Rainer.; Temam, Olivier. (Springer US : Imprint: Springer, 2010)
Processor and System-on-Chip Simulation Edited by: Rainer Leupers Olivier Temam The current trend from monolithic processors to multicore and multiprocessor systems on chips (MPSoC) with tens of cores and gigascale integration makes hardware architecture and software design more and more complex and costly. Therefore, simulation technology has become an extremely important pre-silicon verification and optimization vehicle. Simulation of computer architectures has made rapid progress recently. The primary application areas are hardware/software performance estimation and optimization, as well as functional and timing verification. Recent, innovative technologies, such as retargetable simulator generation, dynamic binary translation and sampling simulation have enabled widespread use of processor and system-on-chip (SoC) simulation tools in the semiconductor and embedded system industries. This book presents and discusses the principle technologies and state-of-the-art in high-level architecture software simulation, both at the processor and the system-on-chip level. " Presents state-of-the-art and future trends in processor and SoC simulation; " Demonstrates how simulation helps to boost hardware and software design productivity; " Addresses simulation requirements and technologies in the multicore context; " Covers system aspects, such as virtual platforms, bus simulation, caches, power, and design space exploration.